The nucleolar DExD/H protein Hel66 is involved in ribosome biogenesis in Trypanosoma brucei - Majeed Bakari-Soale (Nature Portfolio, 2021)
Abstract The biosynthesis of ribosomes is a complex cellular process involving ribosomal RNA, ribosomal proteins and several further trans-acting factors. DExD/H box proteins constitute the largest family of trans-acting protein factors involved in this process. Several members of this protein family have been directly implicated in ribosome biogenesis in yeast. In trypanosomes, ribosome biogenesis differs in several features from the process described in yeast. Here, we have identified the DExD/H box helicase Hel66 as being involved in ribosome biogenesis. The protein is unique to Kinetoplastida, localises to the nucleolus and its depletion via RNAi caused a severe growth defect. Loss of the protein resulted in a decrease of global translation and accumulation of rRNA processing intermediates for both the small and large ribosomal subunits. Only a few factors involved in trypanosome rRNA biogenesis have been described so far and our findings contribute to gaining a more comprehensive picture of this essential process.